ANALISIS PENGELOLAAN DANA INVESTASI ASURANSI JIWA SYARIAH (STUDI KASUS PT. ASURANSI TAKAFUL KELUARGA CABANG MEDAN) - Annisa Zahrina Dharmawan; Zainarti (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine the management of sharia life insurance investment funds and find out the obstacles that occur in managing sharia life insurance investment funds at PT. Medan Branch Family Takaful Insurance. The research method used in this research is a qualitative descriptive approach method. The data collection technique is in the form of interviews and uses primary data obtained directly from PT. Medan Branch Family Takaful Insurance. The subjects in this research were employees and customers at PT. Medan Branch Family Takaful Insurance and the object of this research is the management of investment funds at PT. Family Takaful Insurance Medan Branch. Based on the results of research regarding sharia life insurance investment management funds at PT. Medan Branch Family Takaful Insurance complies with sharia principles which are free from any matters elements of gharar, maisyr and usury which refer to the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and regulations set by the Financial Services Authority (OJK) as well as transparent fund management in accordance with Islamic law. Then in management There are no obstacles to funding, but there were obstacles when Covid-19 emerged in Indonesia where financial dampening in tabarru fund investments has decreased. Companies have to pay customers claims because customer claims increase so costs increase